Problem solving for teams a systematic approach to consensus decision making - Pokras, Sandy (Fifty-Minute series., 1995)
A course which helps you to: discover five tools that help you recognize a problem, learn how to analyze a problem and its cause, find out how to outline your problem solving/decision making, and learn the eight tips that can improve a team's process.